Design and Fabrication of an Improved Vise - Twinamatsiko Smith (Kabale University, 2023)
During manufacturing or machining operations, holding or clamping a job is the basic task for any further process to take place. Clamping of jobs is a difficult task because various shapes, sizes, and materials are used. In a normal bench vice, the operator turns the handle and clamps the job. Here, human effort is involved in the clamp of the job. Human effort applied to clamp the job varies from operator to operator. Less tightening can cause slippage of the job and over-tightening causes damage to the job. All the drawbacks are overcome in the improved vice. In the improved vice, the workpiece is clamped with absolute precision. In the current design which can be mounted on the table or ground directly, it's easy to clamp the workpiece depending on its weight. In this study, different types of vice are reviewed. The conceptual design of the proposed is also presented. The components of the proposed vice are sized using elastic theories of failure. The developed vice design is validated by finite element analysis (FEA). The kinematics of the proposed design is performed in ADAMS. The results indicate the feasibility of the proposed vice and its advantages over existing vice from engineering as well as economic viewpoints.